Advantages of multi-arm non-randomised sequentially allocated cohort designs for Phase II oncology trials - Mossop, Helen; Grayling, Michael J; Gallagher, Ferdia A; Welsh, Sarah J; Stewart, Grant D; Wason, James M S (British journal of cancer, 2022)
Efficient trial designs are required to prioritise promising drugs within Phase II trials. Adaptive designs are examples of such designs, but their efficiency is reduced if there is a delay in assessing patient responses to treatment. Motivated by the WIRE trial in renal cell carcinoma (NCT03741426), we compare three trial approaches to testing multiple treatment arms: (1) single-arm trials in sequence with interim analyses; (2) a parallel multi-arm multi-stage trial and (3) the design used in WIRE, which we call the Multi-Arm Sequential Trial with Efficient Recruitment (MASTER) design. The MASTER design recruits patients to one arm at a time, pausing recruitment to an arm when it has recruited the required number for an interim analysis. We conduct a simulation study to compare how long the three different trial designs take to evaluate a number of new treatment arms. The parallel multi-arm multi-stage and the MASTER design are much more efficient than separate trials. The MASTER design provides extra efficiency when there is endpoint delay, or recruitment is very quick. We recommend the MASTER design as an efficient way of testing multiple promising cancer treatments in non-comparative Phase II trials.